Screening Enamine Fragments Library in the Quest for Novel SOS2 Inhibitors: Pharmacophore Modelling, Molecular Docking, MMGBSA Calculations, and MD Simulation - Abdulrahim A. Alzain; Mohammed A. Almogaddam; Alaa A. Makki; Alaa Edris; Hagar M. Mohamed; Sitelbanat Y. Ehaimir; Shaimaa G. A. Mohamed; Sarah Ameen Taher Felemban; Wedad Hamad Hammad Alshammari; Gamal A. Mohamed; Sabrin R. M. Ibrahim (Journal of Pharmacy and Bioallied Sciences)
Introduction: The son of sevenless (SOS) proteins are rat sarcoma virus nucleotide exchange factors that act as regulatory switches of the rat sarcoma virus (RAS) system through the conversion of the inactive guanosine diphosphate (GDP) bound RAS to the GTP-bound active form, thereby modulating numerous biological events. SOSs contribute in disease incidence and progression in numerous cancers. Currently, SOSs inhibiting strategies deemed a substantial interest in the fight against cancer. Materials and methods: To date, there are various SOS1 inhibitors in the clinical trials, however there are no reported SOS2 inhibitors so far. In this study, we explored the Enamine fragments library against SOS2 through the multidisciplinary computational analysis. Pharmacophore modelling based on the previously published SOS2 inhibitory fragments has shed light on the influential pharmacophoric features. Subsequently, molecular docking and molecular mechanics/generalized born surface area (MM-GBSA) calculations rescored these findings, while molecular dynamics (MD) simulation examined the durability of SOS2-ligand intersections. Results: As a result, three Enamine fragments (Z284596, Z501753, and Z481369) postulated superior docking scores and binding free energies than the crystalized reference bound to SOS2 protein. Conclusion: Furthermore, they postulated a reasonable MD profile. Overall, this study suggested three potential hit fragments with SOS2 inhibitory activity and can be experimentally verified.